Safety and feasibility of subarachnoid block in laparoscopic cholecystectomy (IMC Journal of Medical Science, 2019)
Background and objectives: Laparoscopic surgery is normally performed under general anesthesia (GA), but regional techniques like epidural or subarachnoid block (SAB) have been found beneficial in patients having associated major medical problems. In selected cases, it can be a safe alternative to GA. Hence, the present study was conducted to explore the safety and feasibility of SAB in otherwise healthy individuals undergoing laparoscopic cholecystectomy.Methods: Forty patients undergoing elective laparoscopic cholecystectomy and fulfilling specific inclusion criteria were included in the study. All patients received a segmental (L2-L3 injection) SAB with 3 ml (0.5%) of bupivacaine and 25 microgram of fentanyl. Laparoscopic cholecystectomy was done by standard 4 port technique. Intra-abdominal pressure was kept low at 9-10 mm Hg using CO2 pneumoperitoneum. Patients were followed up at 30 minutes, 4 hours, at the time of discharge and on day 7 after operation. Any unwanted voluntary or involuntary movement or exaggerated diaphragmatic excursion during the operation was monitored. Operation time, operating room (OR) occupancy time, hospital stay, post-operative pain, analgesic requirement, nausea, vomiting, headache, right shoulder pain, wound-related complications and patient satisfaction were recorded.Results: SAB was effective for surgery in all 40 patients. Two patients required conversion to general anesthesia for persisting low oxygen saturation. Hypotension was recorded in 23.7% patients while 10.5% experienced right shoulder pain. Average operating time was 37.3 minutes (21 - 77 minutes). Awkward movement and exaggerated respiratory excursion was noted in 23.7% and 18.4% cases respectively. Only two cases had to undergo (conversion to) GA. Mean period of hospital stay was 29.3 hours. No incidence of any major complication occurred.Conclusion: This study showed that SAB could be used successfully and effectively for laparoscopic cholecystectomy in healthy patients and may be a safe alternative to GA.IMC J Med Sci 2019; 13(1): 006